Natural selection of a GSK3 determines rice mesocotyl domestication by coordinating strigolactone and brassinosteroid signaling - Shiyong Sun (Nature Portfolio, 2018)
Long mesocotyl is a critical trait for the application of rice deep direct seeding or mechanized dry seeding cultivation method. Here, Sun et al. find OsGSK2 is selected for mesocotyl length variation during domestication and it coordinates strigolactone and brassinosteroid signaling to determine mesocotyl elongation.